Implementation of the Principle of Non-Refugee in Handling Rohingya Refugees in Indonesia - Zildjianda, Raesitha; Santriana, Santriana; Nurul Atika , Biyes (Citizenship Education, Faculty of Education, Jambi University, 2025)
Rohingya refugees face significant legal uncertainty regarding their status in Indonesia. One of the main issues faced is the implementation of the principle of non-refoulement, which is an international principle that prohibits a country from returning refugees to their home country if they are at risk of torture, inhumane treatment, or the death penalty. This principle is stated in the 1951 Refugee Convention and its 1967 Protocol, which protects refugees worldwide. The methodology of this research is based on a normative legal research approach. This research will also explore the obstacles and constraints to implementing the Principle of Non-Refulement for Rohingya Refugees in Indonesia and the role of international institutions in supporting the implementation of the Principle of Non-Refulement in Indonesia. Indonesia has a relatively weak implementation of the principle of non-refoulement because until now, Indonesia has not ratified the 1951 Refugee Convention and its 1967 Additional Protocol.On the other hand, Indonesia has not made the refugee issue a top priority in state policy. The support of international institutions in supporting the implementation of the non-refoulement principle in Indonesia is vital. Although Indonesia does not yet have comprehensive legal regulations on refugees, global institutions such as UNHCR, IOM, and other non-governmental organizations play an essential role as partners in helping the Indonesian government implement better policies on refugee protection. With technical assistance, advocacy, and funding, international institutions can help Indonesia fulfill its international obligations more effectively and ensure that refugees in Indonesia receive protection by the principle of non-refoulement